MENINGKATKAN PEMBELAJARAN MATEMATIKA MELALUI PENERAPAN COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) KELAS VI-C UPT. SD NEGERI 01 LIMO KAUM - Meileni Meileni (Ensiklopedia Education Review, 2021)
This research was motivated by the low scores in mathematics at VI-C UPT. SD Negeri 01 Limo Kaum. The purpose of this study is to carry out learning that can improve mathematics learning outcomes through the application of cooperative learning type STAD. This research is in the form of PTK (Classroom Action Research) which consists of 2 (two) cycles. After the first cycle is carried out, then reflection is carried out. The results of the reflection carried out in cycle I conclude that it is necessary to carry out cycle II to improve (1) the implementation of learning which includes: learning media, the active role of researchers in helping students, motivation towards students, building cooperation between students and (2) the results of understanding the lesson mathematics After the second cycle was carried out, the results showed that the use of the STAD Cooperative Learning Type Application. has shown very satisfying results. After the second cycle of learning was carried out, the learning process was using the STAD Cooperative Learning Type Application. very effective to improve learning outcomes in mathematics for students of class VI-C UPT. SD Negeri 01 Limo Kaum. Based on the results of data analysis, in this classroom action research, it was found that the results of student tests at the end of the first cycle of action showed an average value of 75.42 with a percentage of 58.3% absorption. an average of 86.67% with a percentage of absorption reaching 87.5%. Thus it can be concluded that the application of Cooperative Learning Type STAD., In mathematics lessons can improve student understanding and improve student learning outcomes.